2020
DOI: 10.1002/acm2.13086
|View full text |Cite
|
Sign up to set email alerts
|

A phantom study to evaluate three different registration platform of 3D/3D, 2D/3D, and 3D surface match with 6D alignment for precise image‐guided radiotherapy

Abstract: Purpose: To evaluate two three-dimensional (3D)/3D registration platforms, one two-dimensional (2D)/3D registration method, and one 3D surface registration method (3DS). These three technologies are available to perform six-dimensional (6D) registrations for image-guided radiotherapy treatment. Methods: Fiducial markers were asymmetrically placed on the surfaces of an anthropomorphic head phantom (n = 13) and a body phantom (n = 8), respectively. The point match (PM) solution to the six-dimensional (6D) transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…After all, the couch-angle dependency error is difficult to correct but can be minimized to within 1.0 mm. Previously, we have compared the AlignRT accuracy with 2DkV and CBCT using a system that does not have MV cube calibration capability, 21 and the sub-mm differences are consistent with the MV cube calibration.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…After all, the couch-angle dependency error is difficult to correct but can be minimized to within 1.0 mm. Previously, we have compared the AlignRT accuracy with 2DkV and CBCT using a system that does not have MV cube calibration capability, 21 and the sub-mm differences are consistent with the MV cube calibration.…”
Section: Resultsmentioning
confidence: 90%
“…Together with other advancements in SRS treatment, including VMAT SRS planning for multi-lesion treatment using single T A B L E 3 Gated dosimetry equivalency in reference to non-gated delivery using the electronic portal imaging device (EPID) for portal dosimetry measurement. isocenter 21 , the SGRT SRS/SRT procedure has allowed us to treat substantially more cranial lesions and patients as the standard of care in our clinic.…”
Section: C | Clinical Benefits Of the Commissioning In Srs Treatmentmentioning
confidence: 99%
“…Kuo et al reported a phantom study using CBCT, on-board and ceiling-floormounted 2DkV, as well as OSI based on both anatomic-based and point-based registration. 23 Both isocenter and target registration errors were reported and a maximum of 2.5 mm OSI uncertainty was found. To apply SGRT-only patient setup in the clinic to treat brain and HN patient with standard fractionation, a thorough evaluation of SGRT setup accuracy and other advantages is needed with a large clinical dataset.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the study does not involve OSI imaging, it was not under clinical conditions as any interference items, such as facial masks, were excluded. Kuo et al reported a phantom study using CBCT, on‐board and ceiling‐floor‐mounted 2DkV, as well as OSI based on both anatomic‐based and point‐based registration 23 . Both isocenter and target registration errors were reported and a maximum of 2.5 mm OSI uncertainty was found.…”
Section: Introductionmentioning
confidence: 99%
“…Image guidance is used to ensure accurate treatment delivery, accurate target positioning and avoidance of organs at risk. There is a significant body of evidence showing that the use of 2D–2D, combined with 3D–3D match offered by the use of CBCT is associated with increased accuracy of the treatment [ 17 ]. However, this can result in increased time per fraction time, which can lead to increased patient discomfort, and potential movement of the patient.…”
Section: Discussionmentioning
confidence: 99%